Pandangan Hukum Islam terhadap Upaya Membentuk Keluarga Sakinah bagi Wanita Karir - Siti Afiyah; Abd. Hadi (JOSH: Journal of Sharia, 2022)
The sakinah family is a family that has received the grace and blessing of Allah SWT, has been a dream and a dream since planning a wedding and has become the goal of religion and marriage itself. The purpose of this study was to determine the Islamic view of women who have a career, in the concept of forming a sakinah family. So that the family that is built can become a sakinah family, each member must understand and carry out their rights and obligations, as well as a woman who has a dual role in the family where a woman must be a wife and also a mother. The problem here is that a woman with her roles and obligations is required to be able to fulfill the rights of every family member to her. Because Islam itself allows women to work outside the home. The method used in this research is descriptive method. A method to help the researcher know what is happening in the environment under the observer, balanced by analysis and interpretation and in narrative form to complete the picture and obtain significant results. The results of this research and the conclusion is that a woman is allowed to work outside the home, but there are certain limitations that must be obeyed and must be based on permission from her husband. The husband may only forbid his wife to work (by not giving permission) if the work to be carried out by the wife can bring harm to himself and his family. In this condition the husband is obliged to remind him. However, if the work of the wife is to fulfill the necessities of life for herself and her family due to her husband being unable to work to earn a living, either because of illness, poverty or other reasons, then the husband has no right to forbid it.